Efektivitas Media Wordwall terhadap Kemampuan Menyelesaikan Soal Cerita Matematika Kelas 2 SD Negeri Gandekan Surakarta - Aminah, Siti; Prihastari, Ema Butsi; Irmade, Oka (FONDATIA, 2025)
The low performance of second-grade students at SD Negeri Gandekan Surakarta in solving mathematical word problems highlights the need for more communicative and engaging instructional media. This study aims to evaluate the effectiveness of Wordwall media in improving students’ ability to solve mathematical word problems. A quantitative approach was employed using a one-group pretest-posttest design involving 26 students. Data were collected through observation, tests, and documentation, using validated and reliable instruments. The results showed a significant increase in students’ average scores, from 56.12 (pretest) to 82.77 (posttest), following the implementation of Wordwall-based instruction. N-Gain analysis indicated a moderate level of improvement, suggesting that Wordwall is effective in helping students understand and solve mathematical word problems. This study affirms that Wordwall is an effective interactive digital tool that enriches mathematics instruction, enhances conceptual understanding, and encourages active student participation. Keywords: